2007
DOI: 10.1159/000110889
|View full text |Cite
|
Sign up to set email alerts
|

Birth Order and Cord Immunoglobulin E: Results Using a High-Sensitivity Immunoglobulin E Protocol

Abstract: Background: Studies have shown an inverse association between birth order and allergic disease risk; some but not all have shown an inverse association between cord blood immunoglobulin E (IgE) and birth order. We further examined the relationship between birth order and cord blood IgE in a racially diverse birth cohort. Methods: Women were interviewed about their pregnancy history, and their babies’ cord blood was collected to measure total IgE using a high-sensitivity protocol (lower detection limit 0.01 IU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…In contrast to reports from some other regions in the world, we did not find a statistically significant birth order effect in cIgE. Our results are in line with the results reported by Bergmanini [ 20 ] and several other authors [ 7 , 22 , 23 ] who found a nonsignificant relationship between these parameters. Significant differences in cIgE levels by birth order were found only in neonates born by mothers with mIgE < 100 and, non-significant difference in neonates born by mothers with mIgE > 100.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to reports from some other regions in the world, we did not find a statistically significant birth order effect in cIgE. Our results are in line with the results reported by Bergmanini [ 20 ] and several other authors [ 7 , 22 , 23 ] who found a nonsignificant relationship between these parameters. Significant differences in cIgE levels by birth order were found only in neonates born by mothers with mIgE < 100 and, non-significant difference in neonates born by mothers with mIgE > 100.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we found that cIgE levels were not normally distributed and that most cIgE levels were below 0.5 kIU/L, as stated in previous reports [ 20 , 21 ]. The frequency of newborns with detectable levels of cIgE was 26.12% which is higher than frequencies reported in several studies which used the same cut-off values of 0.5 kIU/L [ 21 , 22 ], but lower than in some other [ 7 , 23 , 24 ] and similar to results of Edenharter et al [ 25 ]. Whereas, the mean cIgE level among detectable samples was 1.59 IU/l, with a range of 0.51 to 8.24 kIU/l, similar to findings from Nabavi et al [ 10 ] but lower than the one reported by Goldstein which resulted from a sample taken from a community cohort with high prevalence of asthma [ 23 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…For total IgE levels at birth, one study showed an association between larger sibship size and decreased cord blood total IgE levels [23]. However, other studies, including one in one of our own birth cohorts, did not replicate this protective effect on cord blood IgE levels [26,27]. Furthermore, no evidence for association of larger sibship size on decreased total IgE levels at older ages has been reported [22,28].…”
Section: Discussionmentioning
confidence: 78%
“…According to this theory, maternal immunomodulation acquired through multiple pregnancies might be transmitted to the developing fetus [5-7]. Although a cohort study in the USA found no association between birth order and total cord blood IgE level [8], another recent study reported a significant interaction between birth order and IL13 polymorphisms affecting allergic sensitization: the effect of IL13 was restricted only to firstborn children, suggesting adverse prenatal programming in firstborn offspring [9]. …”
Section: Introductionmentioning
confidence: 99%